Corporate Governance and Firm Risk: Earnings Management as Moderating Variable - Eriandani, Rizky; Wijaya, Melvina Gome; Sulistiawan, Dedhy (Indonesian Journal of Business and Entrepreneurship, 2024)
Background: The research on corporate governance and firm risk is of paramount importance from an economic standpoint, primarily due to its significant influence on company performance and stability. Effective corporate governance can play a pivotal role in mitigating corporate risks.Purpose: This study aims to investigate the impact of many factors related to corporate governance (such as board size, board independence, board meetings, board gender diversity, audit size, audit independence, audit meetings, audit quality, institutional ownership, and largest ownership) and earnings management on company risk. Furthermore, earnings management factors play a role in the connection between corporate governance and firm risk.Design/methodology/approach: The study employed a sample of three companies with the highest assets and three with the lowest assets from each sector listed on the Indonesian stock exchange throughout 2020–2022. For testing purposes, this study uses panel data and moderated regression analysis.Finding/Result: These findings show that several factors impact firm risk, including board meetings, board independence, discretionary earnings management, audit size, audit independence, institutional ownership, and largest ownership. Earnings management can mitigate the impact of audit attributes on corporate risk. Furthermore, studies have shown that earnings management plays a crucial role in reducing the influence of ownership structure on firm risk.Conclusion: The research results show that several proxies of corporate governance are able to reduce company risk. Earnings management further moderates the influence of these factors.Originality/value (State of the art): This research investigates the relationship between firm risk and a broad range of internal governance traits. It is important to note that only a few studies in the literature have examined this relationship because investors are concerned about return volatility, which is a gauge of a company's risk. This research can encourage improvements in corporate governance policies. Managers can use research findings to identify weaknesses in existing governance practices and develop more effective policies for managing risks associated with earnings management practices. Keywords: corporate governance, firm risk, earnings management, audit, company performance